COMPLEMENTATION TO THE "BASIC HYPOTHESIS": REGRESSION TO THE INORGANIC VERSUS SELF - REPRODUCTION - Balazs, Andras (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
We show in this study that the living organism, after its birth, had two routes of time evolution, which is represented at also multicellulars, due to our internal backword time process (introduced originally by Gunji), namely, direct disintegration or a tenous space mapped, metabolism “ based growth and self“ reproduction. We investigate in some details the physical conditions which made (and makes) possible the second route, chosen by Nature, evidenced by organic evolution. We will find that the crucial internal components are informational, classical, additional degrees of freedom, which leads to a matrix structure of the systems phase space and forming our leading principle of internal “self measurement chains, the overall process termed by us endogenous exophysics. We also examine the build up of these crucial informational, ruling (controlling, constraining) biopolymers. We will find that their structure can be described by well known technics of molecular physics (the LMO picture), however, our logical monomeric factorizations, contrary to these technics, is not unitary but projective and is unique. We maintain that the life process could come about only in a mesoscopic structure, allowing for a natural quasiclassical internal dynamics, and also allow for the joint introduction of both underlying quantal, also informational classical observables internally. We conclude that chosing the more difficult and involved life process, as opposed by disintegration, (cell division), had to be a choice of Nature, which we must accept as a natural fact.